Eksplorasi Rafinosa Biji Kapas sebagai Pengganti Formalin dalam Pengawetan Ikan [Raffinose Exploration Cotton Seeds Lieu Of Formalin In Preserving Fish] - Abdul Manan; Khairanita K; Pipin Suciati; Kurnia Ayu K.W; Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Preservation is a human effort to enhance durability and shelf life of the fish that the quality of fish remains in good condition. Irregularities in the use of formalin preservation would endanger the health of consumers. Cottonseed is containing compounds of Raffinose, proteins, fats that are cryoprotectants to cells and antimicrobe, that use of cottonseed to suppress use of formalin as a preservative of fish in the community. The method used by dissolving cottonseeds in organic solvents, where in the organic solvent effective to extract the active ingredients in cottonseed. The results showed use of cotton seed extract is 100% equal to 100% use of formalin in maintaining the quality of the fish. This is evidenced by organoleptic tests, pH and bacterial tests. Expected with these results, cottonseed can be a substitute for use of formalin.